El perspectivismo leibniciano en Baumgarten. Notas sobre el influjo del concepto de pequeñas percepciones en la estética baumgartiana - Incio, Sebastián (Pontificia Universidad Católica del Perú. Departamento de Humanidades, 2022)
In 1735 Baumgarten published his Philosophical Reflections on Poetry. There he develops for the first time the idea of a science of sensibility capable of apprehending the idea of beauty in art; a science which he denominates aesthetics. This quest to determine what beauty is and what the status of aesthetic experience within the edifice of knowledge is seems to be more related to the Leibnizian approaches to sensitivity than to the Wolffian gnoseological framework, not only because of the way in which it deals with the concepts of perfection, beauty and truth, but mainly due to the fact that, in the development of Baumgarten’s research on sensitivity, mechanisms of subjectivation similar to the ones presented by Leibniz seem to be deployed —mechanisms characterized by a strong perspectival background. In view of this, this paper investigates the Leibnizian influence on Baumgartian philosophy, and specifically the question about how the concept of petites perceptions, as a central element of Leibniz’s perspectivist conception,influences the notion of aesthetics developed by Baumgarten.

En 1735 Baumgarten publica su obra Reflexiones filosóficas acerca de la poesía, en ella, por primera vez, desarrolla la idea de una ciencia de lo sensiblecapaz de aprehender la idea de lo bello en el arte, a la cual designará como estética. Esta búsqueda por determinar qué es la belleza y cuál es el estatuto quetiene la experiencia estética dentro del edificio del conocimiento parece estar más relacionado con los planteamientos leibnicianos en torno a la sensibilidad, que con el marco gnoseológico wolffiano, no solo por el manejo que se da de los conceptos de perfección, belleza y verdad, sino porque en el desarrollo de sus investigaciones sobre la sensibilidad parece ejecutarse mecanismos de subjetivación similares, marcados por un fuerte trasfondo perspectivista. En vista de esto, el presente ensayo se pregunta por la influencia leibniciana en la filosofía baumgartiana, específicamente por la cuestión acerca de cómo influye el concepto de pequeñas percepciones, en tanto que elemento central de la concepción perspectivista de Leibniz, en la concepción de la estética por Baumgarten.
Leibnizian Perspectivism in Baumgarten. Notes on the Influence of the Concept of petites perceptions in Baumgartian Aesthetics
Keywords: Petites perceptions; Perspectivism; Beauty; Perfection; Artwork; Pequeñas percepciones; Perspectivismo; Belleza; Perfección; Obra de arte; https://purl.org/pe-repo/ocde/ford#6.03.01